Outcomes and prognostic factors in modern era management of major salivary gland cancer. Issue 8 (August 2015) - Jegadeesh, Naresh; Liu, Yuan; Prabhu, Roshan S.; Magliocca, Kelly R.; Marcus, David M.; Higgins, Kristin A.; Vainshtein, Jeffrey M.; Trad Wadsworth, J.; Beitler, Jonathan J.
Highlights Evaluated outcomes of a recent cohort of patients with major salivary gland cancer. Distant metastasis was associated with deep parotid lobe involvement. Radiation abrogated locoregional recurrence risk from associated factors. Radiation did not reduce distant metastasis risk from associated factors. Distant metastasis remains the primary concern in management of this disease.